DEVELOPMENT OF CARGO TRANSPORTATION SYSTEM BY ROAD ON THE BASIS OF LOGISTICS PRINCIPLES - Tsarenkova, I. M. (Science and Transport Progress, 2017)
Рurpose. The article is aimed to develop and adapt the theoretical and methodological foundations for improving logistics system of cargo delivery by road transport in the framework of the scientific support of formation processes of transport-logistical system of the country. Methodology. The theory of system functioning control requires formalization of connections within the system. The qualitative and quantitative characteristics of entity were performed and the regularities of elements interaction in the system of road goods transportation were found out. The role of the road in transport industry and the influence of transportation and logistics space on the road itself in the process of its functioning were clarified. In the study of this topic the system approach, methods of synthesis and rational problem solving, theory of mass service were used. Findings. The work presents the highway as an element of the cargo transportation system that will make it possible to increase its economic efficiency in a constantly changing environment of transportation and logistics space according to the chosen criterion, the lower total costs to promote material flow. Theoretical-methodological bases of perfection of logistics system of cargo delivery by road transport include substantiation for the use of logistics as an effective control element to reduce the costs associated with goods transportation. They are distinguished by the presence of evidence-based methods for calculating the timing and sequence of execution of road works, logistic integration involved in the carriage of goods of the enterprises, structure and volume of material and accompanying flows and the formation of the logistics chain of its promotion. Originality. The road is represented by the link of single integral process of creation and management of the material flows. We propose formation of sub-system of the elements of road and transportation components with their further unification by a single road transportation system. Inter-connected elements of the system are formalized in the form of dispersed two-phase system of mass service. Each element of the system is evaluated by its own characteristics. Practical value. The practical significance of research consists in possibility of their use by employees of motor transport enterprises, service enterprises, responsible for procurement of production and transportation of products, travel agencies to make science-based decisions in forming the program of road works and to provide alternative opportunities for the rational organization of cargo transportation.